2017
DOI: 10.1186/s40104-017-0192-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of early antibiotic intervention on blood parameters, apparent nutrient digestibility, and fecal microbial fermentation profile in pigs with different dietary protein levels

Abstract: Backgroud: This study aimed to determine the effects of early antibiotic intervention (EAI) on subsequent blood parameters, apparent nutrient digestibility, and fecal fermentation profile in pigs with different dietary crude protein (CP) levels. Eighteen litters of piglets (total 212) were randomly allocated to 2 groups and were fed a creep feed diet with or without in-feed antibiotics (olaquindox, oxytetracycline calcium and kitasamycin) from postnatal d 7 to d 42. On d 42, the piglets within the control or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 41 publications
5
55
1
Order By: Relevance
“…In pigs, antibiotic exposure in early life altered glucose metabolism 35 days after antibiotic withdrawal . Our studies also showed that in‐feed antibiotics treatment in early life had a long‐term effect on serum urea level and fecal AA fermentation products . These results point to the potential long‐lasting effects of early life antibiotic exposure on subsequent host metabolism.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…In pigs, antibiotic exposure in early life altered glucose metabolism 35 days after antibiotic withdrawal . Our studies also showed that in‐feed antibiotics treatment in early life had a long‐term effect on serum urea level and fecal AA fermentation products . These results point to the potential long‐lasting effects of early life antibiotic exposure on subsequent host metabolism.…”
Section: Introductionsupporting
confidence: 63%
“…The present study was part of series of studies designed to evaluate whether EAE has long‐term effects on subsequent amino acid (AA) profiles and gene expression of AA transporters and receptors of pigs and a detailed description of experimental design has been described in our previous study . Briefly, 18 litters of 7‐day‐old crossbred (Duroc × Landrace × Large White) newborn piglets (total 212) were divided into a control group and an in‐feed antibiotic group, with nine litters per group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotics are known to strongly affect the microbiota composition by the depopulation of sensitive bacterial (58,76). This reduction in diversity and bacterial abundances of the gut microbiota disrupts the gut ecosystem and weakens host immunity to pathogens (77,78).…”
Section: Discussionmentioning
confidence: 99%
“…However, with increasing concerns about antibiotic-resistant bacteria that pose a threat to human and animal health, in-feed antibiotics have been banned since 2006 in Europe and 2020 in China [6]. Recent studies have shown that antibiotics can regulate host nitrogen (N) metabolism, partly due to the antibiotic-induced changes in AA fermentation by gut microbiota [7,8]. In this case, optimal CP requirements for piglets might be different in diets with or without antibiotics.…”
Section: Introductionmentioning
confidence: 99%